Diseño de una máquina para la clasificación y distribución automática de paquetes orientada al sector logístico. (2022)
To carry out the project of designing an automated machine for classification and distribution of packages oriented to the logistics sector, which has the purpose of providing a competitiveness and automation tool to SMEs dedicated to the courier or logistics service, a theoretical work was developed. in which it includes: corresponding calculations for the design of a conveyor belt with its mechanical components and relevant calculations for the selection of the parts that act in its operation, the design of the chassis and profile that will support the efforts on the conveyor through methods static and structural analysis. Based on these designs and the search for an automated process, the pertinent simulation of bar code readings is elaborated according to the type of sensor used, in addition to mentioning the decoding of patterns and selecting the appropriate sensor for the activity to be performed. perform, then the programming and equipment to be able to carry it out according to the design parameters and equipment used so that the machine fulfilled the main objective of the work, together with these activities different software was used in order to involve a simulation of some of these processes, as well as plans corresponding to the design of the conveyor and other mechanisms involved in the correct operation of the machine.